Pengaruh Ukuran Partikel Serta Laju Alir Pada Penyerapan Ion Logam Cr6+ Menggunakan Kulit Langsat (Lansium domesticum) - Andini, Namira Tri; Kurniawati, Desy; Zainul, Rahadian; Nasra, Edi (Periodic, 2024)
Chromium metal is a toxic and carcinogenic metal that needs to be addressed. Biosorption  can be used as one method to reduce lead metal level in waters. Biosorpsian is easy and simpler to use, more-ecomomial, and  environmentally friendly because it utilizes microorganisms and biomaterials. The purpose of this study was to determine the effect of particle size and flow rate on the absorption of Cr6+ metal ions using langsat peel as a biosorbent. In this study, Cr6+metal ions biosorption  was carried out using langsat peel with column method at a particle size variation of 106, 150, 250 and 425µm  and a flow rate variation of 1-4 ml/min. the results of this study were obtained optimum conditions at particle size 106 µm and flow rate 2 mL/min with optimum adsorbtion capacity of 5,02363 and 6,96203 mg/g.